LINGKUNGAN BIOLOGI, PERILAKU DAN STATUS GIZI DENGAN KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS HAMADI - Renold Markus Mofu (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
According to the 2020 Annual Parasite Incidence (API) report, the death rate caused by malaria in Indonesia is 1.3% in a ratio of 0.93/1000 population. From these figures, the 2020 API report shows that Papua Province has a malaria death rate of 181.85/1000 population, Jayapura City 57.29/1000, and Hamadi Health Center 315/1000. The purpose of this study was to determine the relationship between the biological environment, community behavior, nutritional status and the incidence of malaria. This study applies analytical observational techniques with case control. There were 102 respondents, consisting of 51 groups of malaria cases and 51 control groups. The sampling technique used is simple random sampling. Statistical test using Chi-square and Logistic Regression. The results of the analysis showed that there were puddles of water, the presence of bushes, the presence of larvae, the use of mosquito repellent, the behavior of being outside the house at night, the behavior of opening the door of the house at night, nutritional status, the behavior of wearing long clothes (p = 0.001- 0.042) correlated with the incidence of malaria. The variables that become risk factors for malaria are activities outside the home and nutritional status (OR = 5,839; 22,413) based on the results of multivariate analysis. Recommendation: Suggestions to reduce the risk of malaria is to change behavior outside the house at night and improve nutritional status.